Plasticity of purine release during cerebral ischemia: clinical implications? - Pearson, T. (J Cell Mol Med, 2007)
Adenosine is a powerful modulator of neuronal function in the mammalian central nervous system. During a variety of insults to the brain, adenosine is released in large quantities and exerts a neuroprotective influence largely via the A(1) receptor, which inhibits glutamate release and neuronal activity. Using novel enzyme‐based adenosine sensors, which allow high spatial and temporal resolution recordings of adenosine release in real time, we have investigated the release of adenosine during hypoxia/ischemia in the in vitro hippocampus. Our data reveal that during the early stages of hypoxia adenosine is likely released per se and not as a precursor such as cAMP or an adenine nucleotide. In addition, repeated hypoxia results in reduced production of extracellular adenosine and this may underlie the increased vulnerability of the mammalian brain to repetitive or secondary hypoxia/ischemia.